Neurotrophic and immunomodulatory effects of olfactory ensheathing cells as a strategy for neuroprotection and regeneration - Denaro, Simona; D’Aprile, Simona; Alberghina, Cristiana; Pavone, Anna Maria; Torrisi, Filippo; Giallongo, Sebastiano; Longhitano, Lucia; Mannino, Giuliana; Lo Furno, Debora; Zappalà, Agata; Giuffrida, Rosario; Tibullo, Daniele; et al. (Frontiers in Immunology, 2022)
Accumulating evidence sustains glial cells as critical players during central nervous system (CNS) development, homeostasis and disease. Olfactory ensheathing cells (OECs), a type of specialized glia cells sharing properties with both Schwann cells and astrocytes, are of critical importance in physiological condition during olfactory system development, supporting its regenerative potential throughout the adult life. These characteristics prompted research in the field of cell-based therapy to test OEC grafts in damaged CNS. Neuroprotective mechanisms exerted by OEC grafts are not limited to axonal regeneration and cell differentiation. Indeed, OECs immunomodulatory properties and their phagocytic potential encourage OEC-based approaches for tissue regeneration in case of CNS injury. Herein we reviewed recent advances on the immune role of OECs, their ability to modulate CNS microenvironment via bystander effects and the potential of OECs as a cell-based strategy for tissue regeneration.